The Use of Crude Fish Oil (CFO) in Vannamei Shrimp (Litopenaeus vannamei) Feed on EPA and DHA Contents - Januar Hadi Prasetyo; Agustono Agustono; Widya Paramitha Lokapirnasari (Department of Aquaculture, 2020)
Omega-3 fatty acids (Alpha-linolenic acid) and omega-6 fatty acids (Linoleic acid) are a group of essential fatty acids. Essential fatty acids are fatty acids that cannot be synthesized by the body so that must be supplied from the diet. One of the sources of essential fatty acids is derived from fish oil. This study aims to determine the effect of Crude Fish Oil (CFO) in the feed to EPA and DHA content in penaeid shrimp meat. The research method used was a completely randomized design. The treatments used are the varying content of Crude Fish Oil (CFO), which are P0 (0%), P1 (2%), P2 (4%), P3 (6%), and P4 (8%). The results of the study showed significant differences (p <0.05) on the content of EPA and DHA in penaeid shrimp meat. The highest content of EPA and DHA found in P4 treatment (8%) and the lowest at P0 treatment (0%). The use of CFO in penaeid shrimp feed need further study related to the growth of shrimps and prawns reproductive cycle to increase the productivity of penaeid shrimp. CFO on feed should be used at a dose of 6%.